Subordinated debt and prompt corrective regulatory action - Douglas D. Evanoff; Larry D. Wall (Federal Reserve Bank of Atlanta, 2002)
Several recent studies have recommended greater reliance on subordinated debt as a tool to discipline bank risk taking. Some of these proposals recommend using subordinated debt yield spreads as additional triggers for supervisory discipline under prompt corrective action (PCA), action that is currently prompted by capital adequacy measures. This paper provides a theoretical model describing how use of a second market-measure of bank risk, in addition to the supervisors' own internalized information, could improve bank discipline. The authors then empirically evaluate the implications of the model. The evidence suggests that subordinated debt spreads dominate the current capital measures used to trigger PCA and consideration should be given to using spreads to complement supervisory discipline. The evidence also suggests that spreads over corporate bonds may be preferred to using spreads over U.S. Treasuries.
Keywords: 330; Bank supervision; Debt